Unveiling Symbolic Violence in the Daily Practices of Journalists in Jakarta - Haresti Asysy Amrihani (Profetik: Jurnal Komunikasi, 2025)
This research uncovers symbolic violence in the working practices of journalists in Jakarta. According to Bourdieu, symbolic violence is violence that is invisible to the naked eye, operates with symbols, and is a form of domination from the powerful one to a dominated individual. The researcher argues that the practices in the media industry in Jakarta cannot be separated from the dominated and dominating parties; in this case, the journalists as a party dominated by media structures and source persons. This research uses a qualitative approach with a critical paradigm with a case study method on journalists in Jakarta. Researcher found the practices of symbolic violence that occurred in six journalists in Jakarta are by giving envelopes containing cash to the journalists for favorable coverage and by allowing them to get money from advertisements in exchange for their unpaid work. Researcher also found that they received luxury goods from one of the source persons who was considered to have contributed to the interests of the person. They do not realize and do not care that they are victims of symbolic violence. Those who are victims of symbolic violence are accused by habitus, economic capital, and cultural capital.